2014
DOI: 10.1371/journal.pone.0103053
|View full text |Cite
|
Sign up to set email alerts
|

Local-Scale Diversity and Between-Year “Frozen Evolution” of Avian Influenza A Viruses in Nature

Abstract: Influenza A virus (IAV) in wild bird reservoir hosts is characterized by the perpetuation in a plethora of subtype and genotype constellations. Multiyear monitoring studies carried out during the last two decades worldwide have provided a large body of knowledge regarding the ecology of IAV in wild birds. Nevertheless, other issues of avian IAV evolution have not been fully elucidated, such as the complexity and dynamics of genetic interactions between the co-circulating IAV genomes taking place at a local-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Similarly, LPAI H5N1 at 0°C and 10°C showed a T‐90 value (90% reduction in infectivity) of 75 days and 16 days respectively in faeces (Nazir et al., ). However, studies on abiotic reservoirs of AIVs like faeces, intact pond water and pond sediments demonstrated that these fomites did not provide sufficient protection for optimum durations to ensure the year‐to‐year preservation of the virus (Keeler et al., ; Nagy et al., ; Nazir et al., ). Detached duck feathers present in the environment might result in longer environmental persistence of the AIVs compared to faeces and contaminated water (Yamamoto et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, LPAI H5N1 at 0°C and 10°C showed a T‐90 value (90% reduction in infectivity) of 75 days and 16 days respectively in faeces (Nazir et al., ). However, studies on abiotic reservoirs of AIVs like faeces, intact pond water and pond sediments demonstrated that these fomites did not provide sufficient protection for optimum durations to ensure the year‐to‐year preservation of the virus (Keeler et al., ; Nagy et al., ; Nazir et al., ). Detached duck feathers present in the environment might result in longer environmental persistence of the AIVs compared to faeces and contaminated water (Yamamoto et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The progressive dilution of infectious faeces in water would reduce the probability of virushost interactions, implying that there should be certain natural mechanisms that concentrate AIVs from water onto bird's bodies, especially the feathers as even unfavourable environmental conditions during summer do not prevent circulation of AIVs in the environment (Hénaux, Samuel, Dusek, Fleskes, & Ip, 2012). The abiotic reservoirs of AIVs studied so far like faeces, intact pond water and pond sediments did not provide sufficient protection for optimum durations to ensure the year-to-year preservation of the virus (Keeler, Lebarbenchon, & Stallknecht, 2013;Nagy, Černíková, Jiřincová, Havlíčková, & Horníčková, 2014;Nazir, Haumacher, Ike, & Marschang, 2011). Feathers could be a potential source of infection for unaffected birds in nature (Yamamoto et al, 2007).…”
mentioning
confidence: 99%
“…This may suggest that Polish 2013-2014-year H5N3 isolates are a “closed circle”, in which genes such as NP underwent complete rearrangement, but PB2-HA gene constellation was preserved for three years, which may indicate their increased compatibility. An extensive reassortment of AIVs at a local level over short time was demonstrated ( 16 , 29 ). On the other hand, circulation of specific gene constellation without reassortment for a prolonged time was also observed ( 4 , 15 ), to which the existence of frozen evolution of AIV may contribute as a result of persistence in the environment without replication ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike various combinations such as H2N2, H3N2, and H1N1, which threaten human health, H11N9 strains have mostly unknown effects for either avians or humans. H11N9 strains were first isolated in Europe (Great Britain) in 1982 [5], after which they were continuously detected through worldwide surveillance, showing low virulence in avians such as in Australia in 1987 and then in 2006, in Europe in 2002-2014 [6][7][8][9][10]; southern Africa in 2008-2009 [11]; Asian countries in 2009 to 2011-2012 [12][13][14]; USA in 2007 [15]; and for the first time in South America in 2014 [16] followed by in 2015 [17].…”
Section: Introductionmentioning
confidence: 99%